FACTORS INFLUENCING THE DECISION TO PURCHASE HALAL PRODUCTS: KNOWLEDGE, PERCEPTION AND RELIGIUS PERSPECTIVE - Tengku Putri Lindung Bulan; Suri Amilia; Meutia Dewi; Safrizal Safrizal; Muhammad Ridwan Verinanda (Jurnal Apresiasi Ekonomi, 2025)
This research aims to analyze the factors that influence consumers in purchasing halal-labeled products in West Langsa District. The method used is quantitative and qualitative data, with data sources consisting of primary data and secondary data. The number of respondents was determined at 100 people, selected using accidental random sampling technique. Data were analyzed using multiple linear regression methods, t test, F test, and coefficient of determination. The results of the t test show that product knowledge and perception of the halal label have a positive and significant influence on the decision to purchase products labeled halal, while religiosity has a positive and insignificant influence on the decision to purchase products labeled halal. The results of the F test show that product knowledge, perception of halal labels, and religiosity together have a positive and significant influence on purchasing decisions for products labeled halal. The independent variable that has the greatest influence on the decision to purchase halal products is product knowledge. It is recommended that companies provide more detailed information on their products, such as composition, benefits, content and so on. In order to give consumers more confidence regarding the products they will use.